Pértiga, Maracay (Venezuela), Instituto Universitario Pedagógico "Rafael Alberto Escobar Lara", Departamento de Castellano y Literatura (Centro de Publicaciones), núms. 4-5 [sin fecha]. - Montes Giraldo, José Joaquín (Thesavrvs, 2023)
Reseñas de revistas.